Consumer Behavior and Competition-Factors of a Successful Marketing Strategy - Duralia Oana (Studies in Business and Economics, 2022)
It is well known that the level of competition in an industry is a key determinant of the marketing strategy for the bidders participating in a market. On the other hand, the consumers’ reactions to the actions of organizations are an indicator to follow when defining the companies’ marketing strategies. The marketing approach to competition issues can be seen differently from an economic theory angle. Thus, while the economic theory argues that finding similar ways of acting is the key to securing a similar position on the market, the marketing theory emphasizes differentiation from competition, even an extreme differentiation from competition, which ensures a favorable positioning in the minds of consumers. This paper aims to explain the link between the level of competition on a market, an organization’s marketing strategy and consumer behavior, as a vector of response to the actions taken by the organization as a supplier, but also as a direct participant in the shaping of the company’s market strategy. The approach will be a theoretical one, coupled with research from secondary data sources that will highlight how European consumers perceive competition in the current economic context.